2013
DOI: 10.1111/codi.12242
|View full text |Cite
|
Sign up to set email alerts
|

The importance of lymph node retrieval and lymph node ratio following preoperative chemoradiation of rectal cancer

Abstract: The cut-off of 12 lymph nodes does not influence survival and should not be considered for cancer-specific prediction of patients having neoadjuvant CRT. In contrast LNR is an independent prognostic predictor of DFS and OS in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
1
25
0
Order By: Relevance
“…Because this study was not prospectively designed, it is subject to potential bias. The cutoff value of LNR is different from other studies (Kang et al, 2011;Klos et al, 2011;La et al, 2013;Madbouly et al, 2013;Nadoshan et al, 2013). In fact, the cutoff value varies among different studies, ranged from 0.07 to 0.6 (Madbouly et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…Because this study was not prospectively designed, it is subject to potential bias. The cutoff value of LNR is different from other studies (Kang et al, 2011;Klos et al, 2011;La et al, 2013;Madbouly et al, 2013;Nadoshan et al, 2013). In fact, the cutoff value varies among different studies, ranged from 0.07 to 0.6 (Madbouly et al, 2013).…”
Section: Discussionmentioning
confidence: 60%
“…The remaining 21 studies were reviewed with full texts, among which two studies had unclear reporting of neoadjuvant therapy, one lacked endpoint data, and five lacked comparison between LNR groups. Finally, 13 studies with 4023 participants were included in the meta‐analysis, and all were published in recent years (from 2011 up to now). Table offers the baseline characteristics of all included studies.…”
Section: Resultsmentioning
confidence: 99%
“…OS, as the primary outcome, was extracted from 11 studies with available data. Among them, eight studies reported high and low LNRs with one cut‐off value, and a pooled HR of 2.94 (95% CI:1.97 to 3.91, P < 0.001) demonstrated that a high LNR is a predictor of poor OS in rectal cancer after neoadjuvant therapy (Figure ). Minor heterogeneity (I 2 < 0.0%, P = 0.949) was found, and a fixed‐effects model was used.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have not demonstrated an association between the number of LNs examined and OS after neoadjuvant CRT. 12,[27][28][29] Although single institution series from tertiary care centers may possess more uniform surgical and pathologic technique, sample size may limit their ability to detect smaller effect sizes due to reduced statistical power. Larger sample size is an advantage of pooled registries and population-based databases.…”
Section: Discussionmentioning
confidence: 99%